2016
DOI: 10.1080/13880209.2016.1258425
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones exert beneficial effects on letrozole-induced rat polycystic ovary syndrome (PCOS) model through anti-androgenic mechanism

Abstract: Context: Soy is the main source of phytoestrogens, which has long been used as traditional food. One major subtype of phytoestrogens includes isoflavones and they are scientifically validated for their beneficial actions on many hormone-dependent conditions. Objective: The present study examines the effect of soy isoflavones on letrozole-induced polycystic ovary syndrome (PCOS) rat model. Materials and methods: PCOS was induced in Sprague–Dawley rats with of 1 mg/kg letrozole, p.o. once daily for 21 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
86
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 35 publications
(36 reference statements)
11
86
1
2
Order By: Relevance
“…Moreover, although testosterone, DHT and letrozole are commonly employed to induce PCOS-like characteristics in pubertal or adult female rodents, it is not well understood whether androgen excess during these time periods results in organizational or activational effects. Indeed, several recent studies have assumed that letrozole treatment of pubertal female rodents causes organizational effects [47][48][49][50]. Given that our study demonstrated that letrozole treatment exerted mostly activational effects during puberty, this finding implies that letrozole treatment needs to be present for the entire duration of the study to effectively model PCOS.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, although testosterone, DHT and letrozole are commonly employed to induce PCOS-like characteristics in pubertal or adult female rodents, it is not well understood whether androgen excess during these time periods results in organizational or activational effects. Indeed, several recent studies have assumed that letrozole treatment of pubertal female rodents causes organizational effects [47][48][49][50]. Given that our study demonstrated that letrozole treatment exerted mostly activational effects during puberty, this finding implies that letrozole treatment needs to be present for the entire duration of the study to effectively model PCOS.…”
Section: Discussionsupporting
confidence: 58%
“…This excessive testosterone cause other problematic issues like acne, hirsutism and hair loss and also inhibits normal ovulation. So, reducing testosterone to the normal healthy level is the prime goal of PCOS treatment.And our study found statistically significant decrease in testosterone values in all treatment levels as 97.34 ± 3.03 (ng/dl) in SIF 0.10 , 89.29 ± 2.71 (ng/dl) in SIF 0.15 and 79.61 ± 2.85 (ng/dl) in SIF 0.20 [25,26]. found similar results on decrease in testosterone levels by using different dosage levels of soy isoflavones for different time periods.…”
supporting
confidence: 61%
“…The structure of daid is similar to 17β-estradiol, which can bind to estrogen receptors (ER) and modulate the cell cycle, survival and apoptosis [34,35]. GBM expresses both ERα and ERβ [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Those signaling pathways induced by moesin phosphorylation needs to be further studied. Even though ERM proteins play important roles in cell division [34][35][36][37]. the specific regulation of moesin on β-catenin-induced cell cycle arrest is worth investigating.…”
Section: Discussionmentioning
confidence: 99%